PERAN KOPERASI PERTANIAN (KOPTAN) MITRA SUBUR DALAM PENINGKATAN PENDAPATAN DAN KESEJAHTERAAN PETANI PADI DI KECAMATAN GUNUNG SUGIH KABUPATEN LAMPUNG TENGAH - Lussy Nurfitasary; Dyah Aring Hepiana Lestari; Ani Suryani (Lampung University, 2020)
The purposes of this research are to compare income of rice farming members and nonmembers of Mitra Subur Agricultural Cooperative, analyze the economic benefits received by members from the cooperative, the contribution of the cooperative economic benefits to members household income, the distribution of members and nonmembers household income, and compare the level of welfare of cooperative members and nonmembers. This research uses a case study method at Agricultural Cooperative of Mitra Subur subdistrict Gunung Sugih, the Central Lampung district and the number of respondents is sixty people that consist of members and nonmembers. Data of this research were collected in February – March 2018 and analyzed descriptively. The reseach results showed that the rice farming income of members and nonmembers of Mitra Subur Agricultural Cooperative in season one was significantly different, while in season two was not significantly different. The economic benefits of cooperative received by members was still considered low and the distribution of remaining business proceeds had not been carried out fairly. The contribution of the cooperative economic benefits to household income of rice farmers members was still relatively low. Additional income from activities outside of the rice farming resulted in higher income inequality of nonmember farmers, while the income inequality of member farmers was lower. Rice farmer members and nonmembers were in the prosperous category, but the welfare level of non members was higher than that of member farmers.Key words: cooperative, income, member, nonmember